2006
DOI: 10.1073/pnas.0602644103
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of the synaptobrevin transmembrane domain

Abstract: The synaptic vesicle protein synaptobrevin (also called VAMP, vesicle-associated membrane protein) forms part of the SNARE (soluble N-ethylmaleimide sensitive factor attachment protein receptor) complex, which is essential for vesicle fusion. Additionally, the synaptobrevin transmembrane domain can promote lipid mixing independently of complex formation. Here, the conformation of the transmembrane domain was studied by using circular dichroism and attenuated total reflection Fourier-transform infrared spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
104
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(114 citation statements)
references
References 69 publications
9
104
1
Order By: Relevance
“…It should be noted that our approach did not allow us to directly assess the conformation of the membrane proximal region of synaptobrevin. A recent study, however, has shown that the transmembrane region of synaptobrevin is tilted at an angle, though it is noteworthy that this study did not propose an interaction of the membrane-proximal region with the membrane (Bowen and Brunger, 2006).…”
Section: Discussionmentioning
confidence: 42%
“…It should be noted that our approach did not allow us to directly assess the conformation of the membrane proximal region of synaptobrevin. A recent study, however, has shown that the transmembrane region of synaptobrevin is tilted at an angle, though it is noteworthy that this study did not propose an interaction of the membrane-proximal region with the membrane (Bowen and Brunger, 2006).…”
Section: Discussionmentioning
confidence: 42%
“…It seems likely that these residues are transiently forced into close proximity at the point of membrane fusion (Tong et al, 2009), but our BiFC analysis might not be able to resolve such interactions on the background of fluorescence from individual, non-complexed VAMP2 molecules interacting via their TMDs. The predicted TMD of VAMP2 is unusually large, and is embedded in the membrane with a tilt with respect to the bilayer normal (Bowen and Brunger, 2006). Thus, the TMD-mediated interaction of VAMP2 molecules identified here by BiFC probably involves a conformation whereby glycine residues oriented toward the helix-helix interface contribute to the packing of two tilted helices; however, additional transient conformations close to the point of membrane fusion might also exist.…”
Section: Discussionmentioning
confidence: 86%
“…But beyond simple localization, tryptophan residues have been hypothesized to play a direct role in facilitating membrane fusion through anchoring, lipid mixing (Hu et al 2002;Jahn and Sudhof 1999;Sutton et al 1998), and imparting an angle to the transmembrane domain (Bowen and Brunger 2006). Interestingly, viral fusion proteins, which must overcome the same fundamental biophysical challenges as SNARE proteins, often have conserved tryptophan residues localized at the membrane interface.…”
Section: Discussionmentioning
confidence: 99%